2015
DOI: 10.1097/pas.0000000000000499
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Biopsy and Radical Prostatectomy Gleason Score Correlation in Heterogenous Tumors

Abstract: When prostate biopsy cores are separately identified in multiple containers, current recommendations are to grade each specimen individually. For treatment algorithms, the highest Gleason score (HGS) is typically used as the overall score, even if a lower score predominates. This practice has the potential to misrepresent the overall cancer in the entire gland for some patients and place them in a higher-grade group. We compare a novel composite Gleason score (CGS), integrating grade patterns from contiguous p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Arias‐Stella et al recently proposed a composite GS which integrates grade patterns from contiguous positive biopsy sites. Composite GS correlated better with RP GS than the highest biopsy GS . Specifically, the former was less likely to be downgraded compared with the latter in RP specimens.…”
Section: Introductionmentioning
confidence: 84%
“…Arias‐Stella et al recently proposed a composite GS which integrates grade patterns from contiguous positive biopsy sites. Composite GS correlated better with RP GS than the highest biopsy GS . Specifically, the former was less likely to be downgraded compared with the latter in RP specimens.…”
Section: Introductionmentioning
confidence: 84%
“…When tumour foci are widely separated, this should be clearly stated in the pathology report (eg, 10 mm (discontinuous)). Arias-Stella et al studied a small series of 40 cases and reported that discontinuous biopsy involvement more commonly reflects a large tumour focus (78%) than multiple small foci (22%) 16. There is no consensus on how widely separated the cancer glands should be to categorise the tumour as ‘discontinuous’.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus on how widely separated the cancer glands should be to categorise the tumour as ‘discontinuous’. Arias-Stella et al used a cut-off of 2 mm as this corresponds to approximately an entire ×10 magnification microscopic field lacking cancer glands 16. However, as in the case of Gleason grading, pathologists should also factor in tumour morphology when determining linear tumour extent in a prostate biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…All these previous studies relate to patient cohorts, and may not be applicable to individual patients, because biopsy GS provides only an estimate of the GS in the prostate due to sampling variation, regardless of the methodology used to assign the GS . In a large series of 15 598 radical prostatectomy specimens, 22% of patients with biopsy GS 4 + 4 were found to have primary pattern 3 (3 + 3/3 + 4) on radical prostatectomy .…”
mentioning
confidence: 99%
“…All these previous studies relate to patient cohorts, and may not be applicable to individual patients, because biopsy GS provides only an estimate of the GS in the prostate due to sampling variation, regardless of the methodology used to assign the GS. 6,[9][10][11] In a large series of 15 598 radical prostatectomy specimens, 22% of patients with biopsy GS 4 + 4 were found to have primary pattern 3 (3 + 3/3 + 4) on radical prostatectomy. 9 Given the sampling error of the biopsy technique, it is unlikely that a patient with a biopsy GS7 (3 + 4)/grade group 2 with only a minor component of pattern 4 would have a worse outcome just because one of the cores happened to have an exclusive small component of pattern 4 cancer.…”
mentioning
confidence: 99%